1988
DOI: 10.1016/0014-5793(88)80828-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and amino acid sequence of human enkephalinase (neutral endopeptidase)

Abstract: We have isolated a cDNA clone encoding human enkephalinase (neutral endopeptidase, EC 3.4.24.11) in a ).gt 10 library from human placenta, and present the complete 742 amino acid sequence of human enkephalinase. The human enzyme displays a high homology with rat and rabbit enkephalinase. Like the rat and rabbit enzyme, human enkephalinase contains a single N-terminal transmembrane region and is likely to be inserted through cell membranes with the majority of protein, including its carboxy-terminus, located ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(86 citation statements)
references
References 16 publications
2
84
0
Order By: Relevance
“…The purified cDNA insert was subcloned in the pCMV eukaryote expression vector according to the manufacturer's instructions (Stratagene, La Jolla, CA). Sequence verification of the resulting plasmid, called pCMV-hNEP, demonstrated that the amplified NEP sequence corresponded exactly to the published one (24).…”
Section: Methodsmentioning
confidence: 64%
“…The purified cDNA insert was subcloned in the pCMV eukaryote expression vector according to the manufacturer's instructions (Stratagene, La Jolla, CA). Sequence verification of the resulting plasmid, called pCMV-hNEP, demonstrated that the amplified NEP sequence corresponded exactly to the published one (24).…”
Section: Methodsmentioning
confidence: 64%
“…This finding raises the question of the existence of such endogenous NEP-ectopeptidase inhibitor in human. And, importantly, sialorphin could spawn a new class of therapeutic compounds, as its target NEP ectopeptidase is highly conserved between species; the rat and human enzymes have high sequence homology (Ն93%) (14,35).…”
Section: Sialorphin An Inhibitor Of the Sp And Me Catabolism By Spinmentioning
confidence: 99%
“…the enkephalins, substance P, atrial natriuretic factor, bradykinin and the chemotactic peptide fMet-Leu-Phe [7,8]. The amino acid sequence of human NEP is identical with that of the common acute lymphoblastic leukemia antigen (CALLA; CD 10) and is highly conserved in different species [9][10][11].…”
Section: Introductionmentioning
confidence: 99%